Construction of a Pseudozyma antarctica strain without foreign DNA sequences (self-cloning strain) for high yield production of a biodegradable plastic-degrading enzyme. Issue 8 (3rd August 2019) - Sameshima-Yamashita, Yuka; Watanabe, Takashi; Tanaka, Takumi; Tsuboi, Shun; Yarimizu, Tohru; Morita, Tomotake; Koike, Hideaki; Suzuki, Ken; Kitamoto, Hiroko
ABSTRACT: The basidiomycetous yeast Pseudozyma antarctica GB-4(0) esterase (PaE) is a promising candidate for accelerating degradation of used biodegradable plastics (BPs). To increase safety and reduce costs associated with the use of PaE, we constructed a self-cloning strain with high-PaE productivity. A Lys12 gene (Pa LYS12 )-deleted lysine auxotroph strain GB4-(0)-L1 was obtained from GB-4(0) by ultraviolet mutagenesis and nystatin enrichment. Subsequently, the PaE gene (Pa CLE1 ) expression cassette consisting of GB-4(0)-derived Pa CLE1, under the control of a xylose-inducible xylanase promoter with Pa LYS12, was randomly introduced into the GB4-(0)-L1 genome. A PaE high-producing strain, PGB474, was selected from among the transformants by high throughput double-screening based on its ability to degrade emulsified polybutylene succinate- co -adipate. Quantitative PCR revealed that four copies of the PaE gene expression cassette were introduced into the PGB474 genome. PGB474 produced 2.0 g/L of PaE by xylose-fed-batch cultivation using a 3-L jar fermentor for 72 h. Graphical abstract: : Pseudozyma antarctica self-cloning strain that produces a high volume of biodegradable plastic degrading enzyme was constructed and selected by high throughput screening.